Corruption in the defence sector and armed conflicts in Nigeria: defining the nexus (2017)
Ordinarily, armed conflicts and corruption appear disparate, but studies have shown that the two concepts are not unconnected. While a comprehensive definition of corruption seems elusive, it is clear that it plays an overarching role before, during and after armed conflicts. In the last decade, Nigeria has suffered immensely from the ills of internal armed conflicts which are easily traced to poor governance, ethnic/religious crises, political and economic inequality, insurgency and so on without any direct link to the role of corruption. This paper attempts a theoretical explanation for the link between armed conflicts in Nigeria and corruption in the Defence sector with specific focus on Boko Haram insurgency in the north-eastern part of Nigeria. The paper examines the capacity of a state to offer good governance and provide security within and around its borders and its direct impacts on the incidence and dynamics of internal armed conflicts. The greed and grievance theory may have proffered the possible nexus between internal armed conflicts and corruption but the exact role of corruption in armed conflicts is situation-specific. While corruption may not necessarily initiate internal armed conflicts, it may be an underlining factor in shaping the incidence, duration and character of armed conflicts. In about a decade since the insurgency started, Nigeria has suffered immensely from and is still grappling with the ills of internal armed conflict. The susceptibility of the Nigerian defence system to corruption and manipulative activities of politicians reveals the ills of corruption before, during and after armed conflict. Corruption in arms and military equipment procurement, lack of transparency in military expenditure and contracts, laundering of proceeds of such corrupt deals by corrupt military officials have far-reaching consequences in exacerbating armed conflicts. This paper focuses on the Armsgate scandal of 2014 and the subsequent report by Transparency International (TI).